Slums : How Informal Real Estate Markets Work - Birch, Eugenie Ladner; Wachter, Susan M.; Chattaraj, Shahana (Book collections on Project MUSE., 2016)
Slums: How Informal Real Estate Markets Work shows that unauthorized settlements in rapidly growing cities are not divorced from market forces; rather, they must be understood as complex environments where state policies and market actors play a role.